ASSESSING THE EFFECT OF THE RGEC METHOD ON FIRM VALUE IN THE INDONESIAN BANKING SECTOR - Magdalena, Jessica; Desyanti, Nurlaili Putri; Meiryani, Meiryani (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2023)
This study aims to find out how the influence of the RGEC method variables includes the risk profile variable, GCG, Profit, and capital variables on the variable value of banking companies in Indonesia in 2019 and 2020. The fixed value was used as the dependent variable and Tobin's Q. Used to assess the banking industry. profit, capital, return and GCG are independent variables. As this is a quantitative study, data analysis was performed using STATA. The research results show that the Risk Profile, GCG, and Earnings partially do not affect firm value. However, there is one influential variable, capital, which influences firm value. When viewed simultaneously, Risk Profile, GCG, Earning, and Capital positively affect the firm value or the RGEC method influences firm value.